Multi-period portfolio optimization under probabilistic risk measure - Sun, Y.; Aw, G.; Teo, K.; Zhu, Y.; Wang, Xiangyu (Academic Press, 2016)
This paper develops a minimax model for a multi-period portfolio selection problem. An analytical solution is obtained and numerical simulations demonstrate the superiority of the multi-period model over its corresponding single period one, as well as over the market index.